DIMENSI METRIK CAMPURAN PADA GRAF DOUBLE FAN - Rahmadi, Deddy (Program Studi Matematika, Universitas Nusa Cendana, 2024)
Let G=(V(G),E(G)) be a simple connected graph. A vertex x∈ V(G) resolves the elements u,v∈ V(G)∪ E(G if d(x,u)≠ d(x,v). The mixed metric dimension, has been recently introduced. The mixed metric dimension (mdim(G)) of a graph G is the cardinality of a smallest set of vertices that resolves each pair of elements from V(G)∪ E(G). In this paper, we will identify the mixed metric dimension on double fan graph.